An INITIAL PERFORMANCE OF OPEN SOURCE ODOO FOR UMKM AT KECAMATAN SEPATAN KABUPATEN TANGERANG - Taswanda Taryo; Jalaludin Jalaludin; Agung Budi Susanto; Sudarno Wiharjo (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2022)
The PKM activity was carried out in Sepatan District, Tangerang Regency, Banten Province. There are micro, small and medium enterprises (UKM) and engaged in food and beverages, where many restaurants operate and are mushrooming in the district. The restaurants implement sales and purchase transactions manually and marketing and looking for buyers should go out into the street so consumers will increase. A problem of the food and beverage restaurant is cash flow management and marketing. An open source Odoo has been aimed at small and large companies having ambitions and desires to improve their performance management. The first stage done was to prepare the Odoo ERP online application for the Kasir Resto post. The formed application was directly submitted to around 20 trainees directly mentored by the Odoo expert. The resto cash flow problems can now be resolved and its marketing strategy in the future can be well planned.